2020
DOI: 10.7554/elife.55177
|View full text |Cite
|
Sign up to set email alerts
|

Diverse and complex muscle spindle afferent firing properties emerge from multiscale muscle mechanics

Abstract: Despite decades of research, we lack a mechanistic framework capable of predicting how movement-related signals are transformed into the diversity of muscle spindle afferent firing patterns observed experimentally, particularly in naturalistic behaviors. Here, a biophysical model demonstrates that well-known firing characteristics of mammalian muscle spindle Ia afferents – including movement history dependence, and nonlinear scaling with muscle stretch velocity – emerge from first principles of muscle contract… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(85 citation statements)
references
References 83 publications
(131 reference statements)
5
76
0
Order By: Relevance
“…Several possibilities were debated at the Neural Control of Movement conference in 2013 without definitive results. We have emphasized that the motor cortex communicates a coded kinematic plan together with stiffness settings that play an essential role in shaping the dynamics in muscle spindles (Blum et al, 2020).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Several possibilities were debated at the Neural Control of Movement conference in 2013 without definitive results. We have emphasized that the motor cortex communicates a coded kinematic plan together with stiffness settings that play an essential role in shaping the dynamics in muscle spindles (Blum et al, 2020).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Importantly, these signals could not have originated within TA, which is slack during the initial portion of this perturbation. Instead, they likely arise from muscle spindle proprioceptive signals [2,52] within the MG and within other muscles within the limbs-and potentially torso and other areas-that are stretched due to the perturbations and which exhibit similar feedback-mediated responses.…”
Section: Plos Onementioning
confidence: 99%
“…13393724) (16,17). Therefore, the muscle spindle model ( 26) was replaced with a multiscale muscle mechanics model in which this burst does emerge (19).…”
Section: Simulation Modelmentioning
confidence: 99%
“…Similarly, studies on muscle spindle firing dynamics are subject to the same interdependence. For example, Blum et al (19) observed a relationship of the Ia afferent response's dynamic index with stretch velocity and initial burst with stretch acceleration. However, the simulated stretch velocity and acceleration were varied with a perfect correlation, thus the observed relations cannot conclusively be linked to either velocity or acceleration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation